State-Level Technological University to Provide Globally Competitive Manpower-The Need of the Hour - Shah, Seema (Journal of Engineering Education Transformations, 2010)
The higher education scene in India has undergone serious and fundamental changes over the past 15 years or so. Quality of engineering education for India is a key priority, but it has been dwindling at the state level with mushrooming of Institutes and there is a dire need to revive it. This article addresses the issue and describes the personal views which have evolved over the length of our career as a teacher and researcher in the education and the industrial sectors. We have proposed the guiding principles, design and architecture of a State Level Technological University (STU) to be established by incorporating best practices of all Universities across the state. We have further explained, how it will impact future quality of engineers and thereby provide globally competitive manpower which is the need of the hour.